2018
DOI: 10.1007/s11419-018-0417-x
|View full text |Cite
|
Sign up to set email alerts
|

Fatal case of poisoning with a new cathinone derivative: α-propylaminopentiophenone (N-PP)

Abstract: PurposeSimilar to synthetic cannabinoids, synthetic cathinone derivatives are the most popular compounds among novel psychoactive substances. Along with a growing number of new cathinones, the number of consumers wishing to enrich their experience with these compounds is also growing, and the same can be said about the growing numbers of poisonings. The reason for overdosing is a lack of consumer awareness regarding composition of the product, with which they experiment, and even more, regarding concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 16 publications
4
12
0
Order By: Relevance
“…(perdeuterated on the diethylpropion moiety) in Several structures have been proposed for the loss of H2O from synthetic cathinones; however, the previous studies did not use of isotopic labeling or HRMS [15,17,28,37,77,78]. Our data supports the mechanism proposed in [61].…”
Section: Dart/esi-q-tofsupporting
confidence: 83%
See 2 more Smart Citations
“…(perdeuterated on the diethylpropion moiety) in Several structures have been proposed for the loss of H2O from synthetic cathinones; however, the previous studies did not use of isotopic labeling or HRMS [15,17,28,37,77,78]. Our data supports the mechanism proposed in [61].…”
Section: Dart/esi-q-tofsupporting
confidence: 83%
“…5b shows the dominant loss of H2O observed at m/z 149.1160 (C10H9D3N + expected at m/z 149.1154; 4 ppm error) from the [M+H] + protonated precursor at m/z 167.1295 (C10H11D3NO + expected at m/z 167.1260; 21 ppm error). This fragmentation behavior is consistent with previous literature for N-alkylated synthetic cathinones[15, 17,28,36,77]. Note that, unlike the fentanyl analogs, neither methcathinone-d3, nor any of the other synthetic cathinones show sodiated adducts ([M+Na] + ) in the full scan mass spectra.…”
supporting
confidence: 91%
See 1 more Smart Citation
“… 56 More recent in vitro studies in neuronal, skeletal muscle and hepatic cells have demonstrated potentially cytotoxic effects of synthetic stimulant exposure, including mitochondrial dysfunction, glutathione depletion, oxidative stress and apoptosis pathway activation, which are aggravated under hyperthermic conditions; however, the extent to which these mechanisms are relevant to their effects in vivo remains unclear. 56 58 …”
Section: Synthetic Stimulantsmentioning
confidence: 99%
“…Case reports have shown synthetic stimulants can induce acute intra-parenchymal and subarachnoid haemorrhages as well as ischemic infarction, 58 and α-PVP has been implicated in ST-elevation myocardial infarction (STEMI) with multiple intra-cardiac thrombi. 59 Intravenous methcathinone (M-CAT) use has been associated with the rare syndrome of manganese-associated Parkinsonism (as the preparation of M-CAT involves use of potassium permanganate) and cognitive impairment, which has been termed ‘ephedrone encephalopathy’.…”
Section: Synthetic Stimulantsmentioning
confidence: 99%